Combination of cellulose nanofiber and artificial fusion protein for biocementation - Nawarathna, Thiloththama Hiranya Kumari; Sakai, Jin; Nakashima, Kazunori; Kawabe, Tetsuya; Shikama, Miki; Takano, Chikara; Kawasaki, Satoru (Frontiers in Built Environment, 2024)
Biomineralization occurring in living organisms is mostly controlled by organic macromolecules such as polysaccharides and proteins. Recently, biomineralization has been attracting much attention as a green and sustainable cementation technique including enzyme-induced carbonate precipitation (EICP), where CaCO3 is formed by hydrolysis of urea by urease in the presence of calcium ions. In this study, we have developed a novel hybrid biocementation method combining CaCO3 and cellulose nanofiber (CNF). In nature, matrix proteins work as a binder at the interface of organic and inorganic materials to form hybrid biomaterials. By mimicking the natural system, we designed an artificial fusion protein to facilitate the deposition of CaCO3 on CNF. Calcite-binding peptide (CaBP) and carbohydrate-binding module (CBM) were introduced in the artificial fusion protein CaBP-CBM to connect CaCO3 and cellulose. The addition of CNF in the EICP system resulted in the formation of a number of small particles of CaCO3 compared to a non-additive system. The addition of the fusion protein CaBP-CBM to CNF led to an increase in the size of CaCO3 particles. Furthermore, the combination of CaBP-CBM and CNF provides higher strength of samples in sand solidification. Therefore, introduction of CNF and the fusion protein would be promising for novel biocementation techniques.